2023
DOI: 10.3390/vaccines11010135
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Routine Use of 15-Valent Pneumococcal Conjugate Vaccine in the US Pediatric Population

Abstract: This study evaluated the clinical and economic impact of routine pediatric vaccination with the 15-valent pneumococcal conjugate vaccine (PCV15, V114) compared with the 13-valent PCV (PCV13) from a societal perspective in the United States (US). A Markov decision-analytic model was constructed to estimate the outcomes for the entire US population over a 100-year time horizon. The model estimated the impact of V114 versus PCV13 on pneumococcal disease (PD) incidence, post meningitis sequalae, and deaths, taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…This study differs from most other reports on PD in the US pediatric population by reporting hospital costs per admission, rather than costs estimated from Markov models of simulated clinical events [18, [20][21][22][23]. These differences in study design make comparisons among studies di cult.…”
Section: Discussionmentioning
confidence: 95%
“…This study differs from most other reports on PD in the US pediatric population by reporting hospital costs per admission, rather than costs estimated from Markov models of simulated clinical events [18, [20][21][22][23]. These differences in study design make comparisons among studies di cult.…”
Section: Discussionmentioning
confidence: 95%
“…In Canada [37] and Greece [60], PCV20 was estimated to be cost-saving compared with PCV15 in a 2+1 schedule. In the United Kingdom (UK), PCV20 2+1 was estimated to be cost-saving compared to PCV13 1+1 and cost-effective compared with PCV20 1+1 [61]. Moreover, a public health impact analysis in the Netherlands and estimated that PCV20 could avert 45,127 pneumococcal cases compared to PCV10 over 5 years [62].…”
Section: Discussionmentioning
confidence: 99%
“…There are few studies that model the usage of PCV15 or PCV20 [ 15 , 16 , 17 ]. One study, developed for the UK, found that PCV20 would save costs and reduce disease [ 18 ]; however, that study focused on adults.…”
Section: Introductionmentioning
confidence: 99%